Expressive writing to improve resilience to trauma: A clinical feasibility trial. (February 2019) - Glass, Oliver; Dreusicke, Mark; Evans, John; Bechard, Elizabeth; Wolever, Ruth Q.
Abstract: Background and purpose: Trauma is highly prevalent, with estimates that up to 90% of the U.S. population have been exposed to a traumatic event. The adverse health consequences of trauma exposure are diverse and often long-lasting. While expressive writing has been shown to improve emotional and physical health in numerous populations, the feasibility and potential effectiveness of a novel expressive writing program provided in a clinical setting to improve resilience is unknown. Our objective was to determine the feasibility and potential effectiveness of a 6-week expressive writing course provided in a clinical setting to improve resilience in individuals with a history of trauma. Materials and methods: This prospective, observational trial of a 6-week expressive writing intervention ( Transform Your Life: Write to Heal ) was conducted in an academic outpatient integrative clinic. Eligible participants were a self-referred sample of 39 English-speaking adults who identified as having had a trauma, or significant emotional/physical upheaval, within the past year. Main outcome measures included: Feasibility : Enrollment, Retention in Program and Trial, Adherence. Acceptability: Adverse Events; Participant Ratings. Primary Psychological Outcome: Connor-Davidson Resilience Scale (CD-RISC). Secondary Psychological Outcomes: Perceived Stress Scale – 10 item (PSS-10); Center for Epidemiologic Studies Depression Scale (CES-D); Rumination Response Scale (RRS). Results: All measures of feasibility including those related to enrollment, retention, and adherence support feasibility. All measures of acceptability including adverse events and participant ratings support the intervention as being safe, well-received and personally valuable. Resilience scores increased from baseline (64.3 ± 14.40) to post-intervention (74.2 ± 13.15), t(37) = 4.61, p < 0.0005; Cohen's d = 0.75. In addition, across the same period, Perceived Stress scores decreased close to a standard deviation (20.5 ± 7.43 to 14.3 ± 6.64), t(37) = −4.71, p < 0.0005, Cohen's d = 0.76; depression symptoms decreased (from 19.0 ± 13.48 to 12.7 ± 11.68), t(37) = −3.21, p = 0.003, Cohen's d = 0.52; and rumination scores decreased from 48.5 ± 12.56 to 39.8 ± 10.07), t(37) = −5.03, p < 0.0005, Cohen's d = 0.82. Effect sizes ranged from medium to large. Conclusion: The Transform Your Life: Write to Heal program is feasible to offer in a clinical setting, was well-received by participants, and demonstrated preliminary findings of effectiveness. Our study suggests that this novel 6-week writing intervention including expressive, transactional, poetic, affirmative, legacy, and mindful writing prompts increases resilience, and decreases depressive symptoms, perceived stress, and rumination in an outpatient sample of those reporting trauma in the past year. The program appears suitable to be evaluated in a larger randomized controlled trial. Highlights: Transform Your Life: Write to Heal program is feasible to implement in outpatient settings. The program was relatively simple to implement and well-received. Participants improved their resilience, depression symptoms, perceived stress and rumination.